Project Based Software Instruction For Future Student Administration Readiness: Pelatihan Perangkat Lunak Berbasis Proyek Untuk Kesiapan Administrasi Siswa Masa Depan - Muhammad Diaz Handa P; Lailul Mursyidah; Intan Nical Wahyu Tifany; Hanny Pradany Putry; Safira Yuliana Putri (Proceedings of The ICECRS, 2025)
General Background The digital era has significantly transformed the landscape of employment and education, requiring robust information and communication technology skills. Specific Background Within Indonesia, numerous secondary learners lack adequate technological capabilities, creating a severe disparity between educational outputs and global market necessities. Knowledge Gap Although human capital theories emphasize active technological learning, there is limited understanding regarding how practical software instruction resolves this regional capability shortage for high school learners. Aims This study analyzes the digital proficiency of learners at SMA Negeri 1 Wonoayu following a targeted Microsoft Word initiative. Results The qualitative case study demonstrates that project-based instruction focusing on toolbar navigation and shortcut application significantly refines document processing and digital administration abilities. Novelty This research specifically identifies practical word processing application as the primary catalyst for overcoming geographical technological skill limitations. Implications Equipping learners with structured technological capabilities prepares them for professional environments, dictating that educational institutions must prioritize competent instructors and relevant facilities. Highlights: Intensive technological instruction refines document formatting and visual design abilities. Active learning methods successfully bridge the technological skills gap for secondary learners. Practical word processing applications prepare individuals for global market demands and higher education. Keywords: Digital Competence, Microsoft Word, Document Processing, Human Capital, Secondary Education